Análisis del talento humano, técnico, económico y logístico en los noticiarios de Lago Sistema Canal 4, y propuesta para mejorar el nivel de audiencia en los habitantes de Nueva Loja, cantón Lago Agrio, provincia de Sucumbios, periodo abril – agosto 2013 - Capa Galarza, Marilu (2014)
Communication is the central part of social or psychological processes involved in the transmission and reception of messages humans. Communication is present in any act, conduct or representation of human activity and all component interaction processes in which man participates. For a large percentage of humanity, television is part of everyday life. Its applications, whether for entertainment or information, oras a tool innumerous activities are numerous and continue to grow. Through a study and analyst is of audiences, which analyzed all involved in the process of generating a television news space, is I can conclude what are the gaps in a media, later to make of effective ly planned a proposal that responds to the problem. The news are considered the main program of a channel according to the writer Omar Rincón, as it works to provide information and a daily viewing public, which is why your presentation should be in accordance with public tastes and preferences of viewer sand executives channel. For this reason it was essential to study and analysis of human talent, technical, economic and logistical Lago Sistema news Channel 4 of the Canton Lago Agrio. As a result it was found that information does not handle spaces audiovisual techniques, human resources does not have the expertise and knowledge. Faced with this reality presents a proposal to improve their hearing.